2013
DOI: 10.1155/2013/201329
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Pattern of Chinese Herbal Products for Diabetes Mellitus in Taiwan: A Population-Based Study

Abstract: Background. Traditional Chinese medicine (TCM), when given as a therapy for symptom relief, has gained widespread popularity among diabetic patients. The aim of this study is to analyze the utilization of TCM among type 2 diabetic patients in Taiwan. Methods. The use of TCM for type 2 diabetic patients were evaluated using a randomly sampled cohort of 1,000,000 beneficiaries recruited from the National Health Insurance Research Database. Results. Overall, 77.9% (n = 31,289) of type 2 diabetic patients utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 47 publications
2
43
1
Order By: Relevance
“…[12] However, the previous study showed that more than half of the patients with DM suffered from one or more microvascular complications during >10 years of follow-up. [28] We tried to compare NVC characteristics of only 1 microvascular complication in patients with type 2 DM, but the sample size of patients with only 1 complication was too small to analyze. Future studies with a larger number of patients with a single microvascular complication would be valuable for evaluating NVC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…[12] However, the previous study showed that more than half of the patients with DM suffered from one or more microvascular complications during >10 years of follow-up. [28] We tried to compare NVC characteristics of only 1 microvascular complication in patients with type 2 DM, but the sample size of patients with only 1 complication was too small to analyze. Future studies with a larger number of patients with a single microvascular complication would be valuable for evaluating NVC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the key independent variables for the utilization of CHP among CRC survivors, we selected the demographic factors according to previous studies 21, 22, 23, 24. Patients were classified, based on age, into one of six groups, as follows: ≤39, 40–49, 50–59, 60–69, 70–79, and ≥80 years.…”
Section: Methodsmentioning
confidence: 99%
“…Shih C-C et al 23) 2012 33) In 1997∼2010, 9.25% patients with newly diagnosed acute myeloid leukemia and received radiotherapy and chemotherapy used TEAM 34) Colon cancer In 2004∼2008, 19.81% of newly diagnosed colon cancer patients used TEAM 35) In 2007, 26.9% of newly diagnosed colorectal cancer patients used TEAM 36) Head and neck cancer In 2000∼2011, 37.51% of newly diagnosed head and neck cancer patients used TEAM 37) Pediatric cancer In 2001∼2011, 62.37% of newly diagnosed pediatric cancer patients used TEAM 38) Breast cancer In 1999∼2008, 81.55% of newly diagnosed breast cancer patients used TEAM 39) In 2007, 35.6% of breast cancer patients used TEAM 40) In 2009, 37.33% of breast cancer patients used TEAM 41) Uterine fibroid In 2000∼2003, 73.33% of newly diagnosed uterine fibroid patients used TEAM 42) In 1996∼2010, 25.84% of uterine fibroid patients used TEAM 43) In 2002∼2010, 87.08% of newly diagnosed uterine fibroid patients used TEAM 44) Prostate cancer In 1996∼2008, 38.8% of prostate cancer patients used TEAM 45) In 1998∼2003, 64.5% of newly diagnosed prostate cancer patients used TEAM 46) In 2003∼2008, 52.6% of prostate cancer patients used TEAM 47) In 2007, 22.4% of outpatients with prostate cancer received prescription of herbal medicine 48) Lung cancer In 1996∼2010, Of the lung cancer patients, 31.17% of the operation patients and 26.32% of the non-operation patients used TEAM 49) Endocrine, nutritional and metabolic diseases, and immunity disorders (3.59%) Hyperlipidemia In 2003∼2009, 82.95% of hyperlipidemia patients used TEAM 50) Diabetes mellitus In 2000∼2011, 20.55% of type I diabetes mellitus patients used TEAM 51) In 1998∼2008, 77.91% of newly diagnosed type II diabetes mellitus adult patients used TEAM 52) Mental disorders (3.10%)…”
Section: 대만의 보편적 Team 이용 관련 연구mentioning
confidence: 99%